Coral reproduction on the world’s southernmost reef at Lord Howe Island, Australia - AH Baird (Inter-Research, 2015)
Despite a recent expansion in the geographic extent of coral reproductive research, there remain many regions in the Indo-Pacific where knowledge is limited. For example, Lord Howe Island is the southernmost reef system in the world (31°S); however, very little is known of the reproductive biology of the coral fauna. Here, aspects of the reproductive biology and the timing of reproduction for 40 of the approximately 65 species that occur on Lord Howe Island are documented. In December 2010, field assessments of the stage of gamete maturity in Acropora spp. colonies suggested that 5 species spawned in December 2010 and 11 in January 2011. In January 2012, similar sampling suggested that 12 Acropora species spawned in January and 1 in February. In addition, 11 species from 10 genera broadcast spawned gametes from 17:30 to 24:00 h in January 2012, 10 to 12 d after full moon. Goniastrea favulus was inferred to spawn prior to 17:00 h, 6 to 12 d after full moon and Porites heronensis released brooded larvae. The reproductive biology of 3 other brooding species was examined using dissections and histology monthly for 1 yr from April 2011. Of these, Seriatopora hystrix contained planulae between November 2011 and March 2012, Stylophora pistillata contained planulae between November 2011 and February 2012. No eggs or planulae were observed in Pocillopora damicornis. In conclusion, the spawning patterns on Lord Howe Island are consistent with other locations in the Indo-Pacific: multi-species synchronous spawning episodes occur after full moons, when water temperatures are relatively high.